Analysis and Design Optimization of a Hybrid VO2/Silicon2 $×$ 2 Microring Switch - L. Sanchez; S. Lechago; A. Gutierrez; P. Sanchis (IEEE Photonics Journal, 2016)
The metal-to-insulator transition (MIT) property of vanadium dioxide (VO2) has recently been used in several application fields such as plasmonics, sensing, metamaterials, and optical modulation. Due to the MIT nature, VO2 allows a huge change in its complex refractive index that can be electrooptically controlled. In this paper, the analysis and design optimization of a 2 × 2 microring switch based on a hybrid VO2/silicon waveguide structure is addressed. Switching is achieved by exploiting the change in both absorption loss and phase shift that occurs in VO2 when changing from the insulating to the metallic state. The device is optimized to minimize insertion losses and crosstalk. An active length of only μm is required to achieve a data throughput rate higher than 500 Gb/s at a single optical wavelength.